EVALUATING FLIPPED CLASSROOM APPROACH IN EFL STUDENTS READING CLASSES - Maharsi, Ista; Wijayanti, Yunita Rizky; Astari, Tri Retna (LLT Journal: A Journal on Language and Language Teaching, 2021)
This paper examines the implementation of flipped classroom approach in an EFL private university in Indonesia. It explores how this approach impacts on students reading comprehension and how students perceive the flipped classroom in their learning process. Under the mixed method design, data were collected from pre-test and post-test, classroom observations, and students reflective notes. There were 47 students in the experimental groups and 25 students in the control groups. Those 72 students from both groups took a compulsory 2-credit Intensive Reading Course in their first year in the pre-service teacher training. Both groups were taught the same reading skills and tasks comprising of the total 14 meetings for the whole semester and each meeting took 100 minutes. Results indicate that students in the traditional classrooms gained an increase in their post-test score compared to their counterpart in the flipped classrooms. This might relate with the teacher-led instructions and scaffolding which are commonly conducted in traditional classrooms where students listen to teachers explanation and students can ask directly. Other reasons arehesitation/inconvenience in using technology in learning, task-related time management, and technology-related workload. However,for many students flipped classrooms are perceived as promoting independent, responsible, active, and free learning. Both benefits and drawbacks of flipped classrooms in this context are also discussed